Organizational and media stress among professional football players: testing an achievement goal theory model - Kristiansen, E.; Halvari, H.; Roberts, G. C. (Scandinavian Journal of Medicine & Science in Sports, 2012)
The purpose of this study was to investigate media and coach-athlete stress experienced by professional football players and their relationship to motivational variables by testing an achievement goal theory (AGT) stress model. In order to do so, we developed scales specifically designed to assess media and coach-athlete stress. Eighty-two elite football players (Mage=25.17 years, SD=5.19) completed a series of questionnaires. Correlations and bootstrapping were used as primary statistical analyses, supplemented by LISREL, to test the hypotheses. Results revealed that a mastery climate was directly and negatively associated with coach-athlete stress, while a performance climate was directly and positively associated with coach-athlete stress. In addition, an indirect positive path between the performance climate and media stress was revealed through ego orientation. These findings support some of the key postulates of AGT; a mastery climate reduces the perception of stress among athletes, and the converse is true for a performance climate. Coaches of elite footballers are advised to try to reduce the emphasis on performance criteria because of its stress-reducing effects.